SH 0 guided wave interaction with a crack aligned in the propagation direction in a plate - Ratassepp,M; Lowe,MJS (2009)
Ultrasonic guided waves are currently of interest for structural health monitoring of large structures such as storage tanks and pipelines. This study focuses on the scattering of the fundamental horizontal shear (SH 0) mode at a through-thickness notch or crack in a plate whose alignment is in the direction of the wave propagation. The reflection and diffraction of the wave at a crack are examined using 2D finite element simulations. It is shown that the main reflection is generated by Rayleigh-like surface waves created on the faces of the crack, which radiate energy back into the plate. The amplitudes of the reflected and diffracted signals are verified experimentally. © 2009 American Institute of Physics.